The impact of the Covid-19 pandemic on social inequalities in international student mobility: a scoping review - Joana Almeida; Nicolai Netz; David Nika; Ewa Krzaklewska; Joyce Aguiar; Alina Botezat; Thais França; Suvi Jokila; Bernhard Streitwieser; Rúna Vigdís Guðmarsdóttir; Daniel Malet Calvo (Comparative Migration Studies)
Abstract This systematic literature review sheds light on social inequalities in students’ access to and experiences of international student mobility (ISM) in the context of the Covid-19 pandemic. Following a scoping approach based on the 2020 PRISMA guidelines, it synthesises 48 empirical studies published in the most intense phase of the Covid-19 pandemic, namely between January 2020 and June 2022. The findings demonstrate that the social inequalities that became visible due to the pandemic relate to different study abroad phases (before, during, and after ISM) and levels of analysis (micro, meso, and macro level). At the micro level, the four most frequently examined dimensions of social inequality comprise (1) students’ mental health and wellbeing, (2) experiences of exclusion, discrimination, or racism, (3) financial vulnerability, and (4) determinants of study abroad plans. At the meso level, the reviewed studies mostly address (5) institutional support services. Macro-level studies focus on (6) governmental policies and negative public perceptions of international students. The review demonstrates that the pandemic not only exacerbated previously known social inequalities, but also created new ones, which were experienced by students mostly whilst they were abroad. It also highlights that different social inequalities are connected to specific study abroad phases, student groups, and social structures. Moreover, it shows that the inefficiency or lack of support of both meso- and macro-level structures may enhance the social vulnerability of specific groups of international students. Overall, the review indicates that during the most intense phase of the Covid-19 pandemic, scholarly attention has shifted from inequalities in access to ISM to the lived experiences of international students.